Prinsip Akuntabilitas dan Transparansi Terhadap Pengelolaan Keuangan Usaha Ritel Pakan Ternak UMKM Lampung Barat - Bela Mutiara; Hurian Kamela (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2026)
This study aims to analyze the influence of accountability and transparency principles on financial management in feed retail micro, small, and medium enterprises (MSMEs) in West Lampung Regency. Accountability and transparency are considered essential aspects of good governance implementation, which play a crucial role in building trust and improving the financial effectiveness of small enterprises. The research applies a quantitative approach through a survey distributed to customers and farmers using a Likert-scale questionnaire. Data were analyzed using multiple linear regression to examine the effect of accountability and transparency on financial management perception.. The results indicate that both variables have a positive and significant influence on customers’ and farmers’ perceptions. The implementation of accountability and transparency strengthens public trust and enhances the professionalism of financial management practices in MSMEs, particularly in feed retail businesses.